Luminescent host-guest systems based on coordination compounds: synthesis, characterization, and applications - Vilela, Raquel Riciati do Couto (2022)
Host-guest materials are under fast development and constitute an attractive research topic on account of the versatility and wide range of applications they serve. In many of these applications, the photoactivity of coordination compounds embedded in a solid matrix is exploited. Besides attaining application versatility (as opposed to their study in solution), the appropriate dispersion or binding of these molecular species in solid matrices offers the possibility of protecting them from vibronic coupling with solvent molecules, preventing self- quenching processes, increasing their photostability and biocompatibility. This doctoral work was dedicated to the synthesis and investigation of the photophysical properties of Ir(III) complexes, in solid state and solution, as well as the design of applications based on their derived host-guest materials, which were obtained via sol-gel methodology. Three different approaches were explored: i) Synthesis of highly luminescent hybrid organosilicate materials based on the immobilization of the complex [Ir(Fppy)2(dmb)]+ in the GPTS:TEOS matrix; ii) Preparation of MCM-41-type mesoporous nanoparticles doped with amphiphilic [Ir(NC)2(dnbp)]+ complexes via templated synthesis and iii) Surface modification of MCM-41 nanoparticles and incorporation of Ir(III) complexes of the series [Ir(NC)2(dmb)]+ for applications in photodynamic therapy. The characterizations of the synthesized complexes, as well as of the materials derived from them, were carried out by conventional techniques such as X-ray diffraction, microscopy (TEM and confocal fluorescence microscopy), FTIR, Raman, dynamic light scattering (DLS), as well as optical (UV-VIS, PL and PLE) and nuclear magnetic resonance (NMR) spectroscopic techniques. Altogether, the experimental strategies used in this work stands as an advance in the design of photo-functional materials with promising applications in optical sensors, luminescent devices and photodynamic therapy.